L.A. rebellion creating a new black cinema : DVD anthology 1971-2006 - Horak, Jan-Christopher 1951-; Field, Allyson Nadia 1976-; Stewart, Jacqueline Najuma 1970- (UCLA Film & Television Archive, 2015)
"The group of Black filmmakers that have come to be known as the L.A. Rebellion created a watershed body of work that strives to perform the revolutionary act of humanizing Black people on screen. The filmmakers in this group met as students in film school at the University of California, Los Angeles, between the late 1960s and the mid-1980s."--booklet. This collection contains this broad representative sampling of their projects, as were exhibited in the film exhibition
1,33.1 Aspect Ratio
Disc one: Africa and diaspora, Disc two: we are family, Dic three: day by day ; educational three-disc box set features: Twenty-five student short films, Digital video and audio remastering by UCLA Film & Television Archive, Essay by L.A. rebellion curator and UCLA Film & Television Archive Director Jan-Christopher Horak
Keywords: African Americans / Drama; African Americans in motion pictures; African American motion picture producers and directors / California / Los Angeles; African Americans in the motion picture industry / California / Los Angeles; African American motion picture actors and actresses / California / Los Angeles; Motion pictures / California / Los Angeles; Film; DVD-Video